An equation is shown below: 6(2x – 11) + 15 = 3x + 12 Part A: Write the steps you will use to solve the equation, and explain each step. (6 points) Part B: What value of x makes the equation true? (4 points)

(1) Answers

I am going to use DCVIMS. I would first distribute the parenthesis. I would combine like terms. I would put the variables on both sides. I would do the inverse. I would put my final answer. Then substitute to check if it is correct! :D 6(2x−11)+15=3x+12 Simplify both sides of the equation. 6(2x−11)+15=3x+12 Simplify 6(2x−11)+15=3x+12 (6)(2x)+(6)(−11)+15=3x+12 (Distribute) 12x+−66+15=3x+12 (12x)+(−66+15)=3x+12 (Combine Like Terms) 12x+−51=3x+12 12x−51=3x+12 Subtract 3x from both sides. 12x−51−3x=3x+12−3x 9x−51=12 Add 51 to both sides. 9x−51+51=12+51 9x=63 Divide both sides by 9. 9x / 9 = 63 / 9 x=7 Plug in 7 to the orginal equation to make sure your answer is right! Hope this helped! :D :D

Add answer